Willingness to pay for conservation of mangrove forest in Kuala Perlis, Malaysia - Bakti Hasan-Basri; Zaiton Samdin; Awang Noor Ghani (Penerbit Universiti Kebangsaan Malaysia, 2020)
Mangrove forest provides ecosystem services for human well-being such as fish and non-fish products, timber and non-timber products, medical plants, and dyes. Despite the important services provided, mangrove forest size in the country is reducing at an alarming rate. The mangrove forest is often overlooked in policy decision makings because the ecosystem services' monetary values are not available in the market. Hence, we undertake this study to value the benefits of Mangrove Forest Ecosystem Services in Kuala Perlis, Perlis. We used the double-bounded Contingent Valuation Method (CVM) to value the ecosystem services provided. We interviewed 256 respondents, asking them whether they are willing to donate to the mangrove conservation program at various bid prices. Besides, we also sought their opinions on issues related to mangrove forest. The results show that the respondents are willing to donate up to MYR18.31 for the mangrove forest conservation program. Considering 75% of Perlis' adult populations are willing to donate, the donation's total collection would be MYR3,453,724 or MYR81,861 per hectare per year. The amount of respondents' donation is found to be positively correlated to the variables of the conservation program. This finding provided an important message to policymakers on managing the fund of mangrove forest conservation.